1977
DOI: 10.1080/01916122.1977.9989150
|View full text |Cite
|
Sign up to set email alerts
|

Angiosperm pollen zonation of the continental cretaceous of the Atlantic coastal plain and its application to deep wells in the Salisbury embayment

Abstract: This paper presents and illustrates an informal paly-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
254
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(261 citation statements)
references
References 28 publications
6
254
1
Order By: Relevance
“…Lower Cretaceous sedimentary rocks assignable to pollen zones II-A and II-B (lower Albian and lower to middle Albian) as designated by Brenner (1963) and Doyle and Robbins (1977) crop out in the Hopewell area Progressively younger Cretaceous sediments crop out northward along the inner Coastal Plain outcrop belt. This distribution is the basis for the rolling depocenter concept presented by Reinhardt and others (1980a), in which the areal extent of each successively younger center of deposition during Cretaceous time appears to be displaced northward into the Salisbury embayment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower Cretaceous sedimentary rocks assignable to pollen zones II-A and II-B (lower Albian and lower to middle Albian) as designated by Brenner (1963) and Doyle and Robbins (1977) crop out in the Hopewell area Progressively younger Cretaceous sediments crop out northward along the inner Coastal Plain outcrop belt. This distribution is the basis for the rolling depocenter concept presented by Reinhardt and others (1980a), in which the areal extent of each successively younger center of deposition during Cretaceous time appears to be displaced northward into the Salisbury embayment.…”
Section: Discussionmentioning
confidence: 99%
“…Lower Cretaceous sedimentary rocks, the Potomac Formation, are assignable to pollen zones II-A and II-B of Doyle and Robbins (1977) and Brenner (1963). These rocks are now known to extend southward to include the Hopewell area Marine sections of the Aquia (Paleocene) and Nanjemoy (Eocene) Formations crop out in the central and eastern parts of the study area Sedimentary structures within both units, as well as within the remainder of the Tertiary marine section, indicate a rapid westward shallowing toward the present Fall Zone.…”
Section: Stratigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…Farley and Dilcher (1986) reported a palynoflora from a lignitic clay exposed a few meters above the leaf-bearing horizon at Rose Creek and concluded that this palynoflora and other assemblages from the Dakota Formation of Kansas indicate a Cenomanian age. Examination of the species list presented by Farley and Dilcher (1986) indicates a probable correlation with Zone III of the Atlantic Coastal Plain, considered early to middle Cenomanian in age by Doyle and Robbins (1977); in addition, some pollen species listed for Rose Creek have their first occurrences within the Western Interior in rocks dated as Cenomanian on the basis of marine invertebrates (see below). A Cenomanian age for the Rose Creek locality is indicated by the combined occurrence of (1) (Doyle and Robbins, 1977;Hedlund, 1966).…”
Section: Criteria For Classificationmentioning
confidence: 99%
“…Examination of the species list presented by Farley and Dilcher (1986) indicates a probable correlation with Zone III of the Atlantic Coastal Plain, considered early to middle Cenomanian in age by Doyle and Robbins (1977); in addition, some pollen species listed for Rose Creek have their first occurrences within the Western Interior in rocks dated as Cenomanian on the basis of marine invertebrates (see below). A Cenomanian age for the Rose Creek locality is indicated by the combined occurrence of (1) (Doyle and Robbins, 1977;Hedlund, 1966). Consistent with a Zone III age is the high diversity and high relative abundance of simple, pinnately veined angiosperm leaves at Rose Creek, because similar assemblages are not known from the Atlantic Coastal Plain until Zone III (Upchurch and Wolfe, 1987b ).…”
Section: Criteria For Classificationmentioning
confidence: 99%